Geoeconomic Statecraft and The Stability Paradox: Russian Energy Policy, 2024–2025 - Mohamad, Amirunnaufal; Aurora, Allynka First (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2026)
This article analyzes Russia’s energy policy in 2024–2025 through a geoeconomic statecraft framework that integrates asymmetric interdependence, state capitalism, and identity-based foreign policy. Existing scholarship has analyzed these dimensions in isolation, leaving unexamined how their interaction generates contradictory stability outcomes during periods of accelerated market adjustment. The study addresses how Russian energy strategy operates not to maximize commercial returns but to preserve regime resources and generate political leverage via pricing, infrastructure control, and selective rent-sharing with key partners. Using qualitative analysis of policy documents, bilateral energy agreements, and multilateral forum proceedings, the article finds a stability paradox: measures strengthening Russia’s domestic position—fiscal capacity and elite cohesion—simultaneously amplify global instability through supply uncertainty, infrastructure politicization, and accelerated counter-diversification by importers. The 2024–2025 period reveals a dual adjustment where European vulnerability-reduction efforts and Russian market reorientation generate new distributional conflicts even as older dependencies diminish.